Orgaran (Org 10172) or Heparin for Preventing Venous Thrombosis after Elective Surgery for Malignant Disease? A Double-Blind, Randomised, Multicentre Comparison - Gallus, A; Cade, J; Ockelford, P; Hepburn, S; Maas, M; Magnani, H; Bucknall, T; Stevens, J; Porteous, F; (ANZ-Organon Investigators’Group) (Thrombosis and Haemostasis, 1993)
This double-blind, randomised, multicentre trial in 513 patients having elective surgery for intra-abdominal or intrathoracic malignancy compared the efficacy and safety of venous thrombosis (VT) prophylaxis using 750 anti-factor Xa units of Orgaran (a mixture of low molecular weight heparinoids) given subcutaneously (sc) twice-daily with that of twice-daily injections of 5,000 units Standard heparin. The main study endpoints were the development of postoperative VT detected by 125I-fibrinogen leg scanning, and the onset of clinically significant venous thromboembolism or bleeding. “Intent to treat” analysis showed a statistically non-significant trend towards less VT during Orgaran prophylaxis (10.4%) than after heparin (14.9%) and there was no difference in bleeding complications between the two study groups. Results remained similar if only patients who completed the intended course of therapy (“compliant patients”) were analysed. Other trials have shown that Orgaran prevents VT after hip surgery and stroke. We now show it is also safe and effective in patients having major surgery for cancer.